Does the Democratization of Polities Entail the Democratization of Citizenship Education? A Theoretical Framework for Researching the Democratic Quality of Citizenship Education in Transformation Countries and Elsewhere - Hippe, Thorsten (JSSE - Journal of Social Science Education, 2008)
In the last 30 years, the process of institutional democratization prevailing in Western Europe since at least the end of World War II has spread to Southwestern, Southeastern and Eastern European countries. To what extent has this democratic transformation of polities been followed by a genuinely democratic transfor-mation of citizenship education in these countries? Unfortunately, recent research on citizenship education does not provide a satisfactory answer, because it has mainly focused on institutional and organizational issues. Nothing was said about the question how well-sounding, but quite general – and therefore ambigu-ous – officially proclaimed goals and contents of citizenship education in transformation countries are educa-tionally construed in textbooks and the teaching practice. However, there are quite a few empirical examples and indications which clearly show that citizenship education in transformation countries (and elsewhere) shows a number of facets which are hardly in line with core democratic values. Therefore, this article pro-poses a theoretical framework for systematically researching the democratic quality of citizenship education in transformation countries (and elsewhere). With recourse to Max Weber`s analytical concept of ideal-types, this framework differentiates between a democratic and a non-democratic ideal-type of citizenship education (as outer points of a continuum between them). These two ideal-types of citizenship education are character-ized by structurally different ways of thinking about 1) human rights, 2) international relations, 3) current insti-tutions and norms, 4) authoritarian political structures and human rights violations in the history of the coun-try, and 5) differences in society.